1997
DOI: 10.1038/sj.onc.1201225
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Neogenin, a DCC-like molecule, has four splice variants and is expressed widely in the adult mouse and during embryogenesis

Abstract: Neogenin is a member of the N-CAM family of cell adhesion molecules and is closely related to the DCC tumor suppressor gene product. Recently, it has been demonstrated that the DCC/Neogenin subfamily plays a key role in axonal guidance within the embryonic nervous system, however little is known about the function of DCC or Neogenin in non-neuronal tissues in vertebrates. To gain an understanding of Neogenin function outside of the nervous system we have cloned and sequenced the mouse homologue of Neogenin. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
64
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 23 publications
(37 reference statements)
2
64
0
Order By: Relevance
“…Neogenin is a membrane protein widely expressed in different tissues including skeletal muscle and liver (22)(23)(24). It is the classical receptor for netrins as well as repulsive guidance molecule a (RGMa), a close family member of HJV (3)(4)(5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neogenin is a membrane protein widely expressed in different tissues including skeletal muscle and liver (22)(23)(24). It is the classical receptor for netrins as well as repulsive guidance molecule a (RGMa), a close family member of HJV (3)(4)(5).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to BMPs, our previous studies showed that HJV also interacts with neogenin (7). Neogenin is a transmembrane protein widely expressed in different tissues including skeletal muscle and liver (22)(23)(24). It is the classical receptor for netrins as well as RGMa (25,26).…”
mentioning
confidence: 99%
“…Furthermore, vascular smooth muscle cells are attracted by and adhere to netrin-1 in a neogenin-dependent manner . Neogenin morphant zebrafish display an aberrant neural tube and defects in somitogenesis, suggesting possible roles in convergent extension and/or cell polarity during formation of the rostrocaudal axis (Mawdsley et al, 2004).Neogenin is expressed throughout the developing mouse embryo but is at high levels in developing skeletal muscle; netrin-1, netrin-3, and RGMc are also expressed in premuscle masses of the mouse embryo Keeling et al, 1997;Wang et al, 1999;Kuninger et al, 2004;Niederkofler et al, 2004;Fitzgerald et al, 2006;Rodriguez et al, 2007). We recently showed that mouse myoblast cell lines and cultured primary myoblasts derived from satellite cells express netrin-3 and neogenin and that these factors promote formation of multinucleated myotubes .…”
mentioning
confidence: 99%
“…Netrins are a conserved family of canonical guidance cues, functioning as either chemoattractants or chemorepellents in a variety of different species (6 -14). Several vertebrate receptors of Netrins have been identified such as deleted in colorectal cancer (DCC) 4 (13,15), Neogenin (15,16), Uncoordinated-5 (UNC5) (17,18), and Down syndrome cell adhesion molecule (DSCAM) (19,20). Although DCC/UNC40 can mediate attraction and UNC5 mediate repulsion by itself (1,13,15,18,(21)(22)(23)(24), assembling of appropriate receptor complexes is essential for the growth cone steering decision in Netrin signaling.…”
mentioning
confidence: 99%